Intraday liquidity modelling using statistical methods - Vojtková, Mária; Mihalech, Patrik (Publishing House of Wroclaw University of Economics and Business, 2023)
The correct approach to liquidity risk management in banks is essential for securing their financial stability. The position of liquidity risk among the rest of bank risks is specific because the negative outcome is not just a loss, but directly the bankruptcy of the institution. Such an occurrence might start a chain reaction and bring uncertainty into the entire financial system. This paper focused on one source of liquidity risk, i.e. management of liquidity throughout the day. The management of intraday liquidity is related to cash inflows and outflows occurring during the business day, their timing and settlement. In 2013, the BCBS published the document Monitoring tools for intraday liquidity management, often referred to by the regulatory authorities. It offers basic concepts of intraday liquidity monitoring and sketchily defines stress scenarios. The author suggests possibilities of how to perform intraday liquidity stress testing in a bank, which is often required by supervisors, even though no detailed approach or methodology as to how to proceed was introduced by the regulators. The research was carried out on anonymised data of cash inflows and outflows recorded on a central bank reserves account of one of the Slovak commercial banks. Both a base and four stress scenarios were developed and suggested for the better understanding of expected cashflows in standard conditions and during stress. The author’s aim was to develop scenarios in a non-traditional way by means of a basic and EWMA historical bootstrap simulations, respectively. Stress scenarios are supposed to simulate reputation crisis, disruption in RTGS payment system, increased deposit outflows and bank run. The purpose of the proposed intraday liquidity monitoring scenarios was to strengthen resilience not only for a concrete bank, but also the entire financial system. Intraday liquidity monitoring is a key factor in securing stability of the financial sector.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 151-178
Keywords: liquidity risk in bank; intraday liquidity; bootstrap simulation; stress testing